Analisis Stilistika Bahasa Slang Digital dan Implikasinya terhadap Etika Berbahasa Siswa SMA Kelas 11 Primbana - Lasmina Boru Sinaga; Sarma Panggabean; Renita Br Saragih (LPPM Universitas HKBP Nommensen, 2026)
This study aims to describe the forms and meanings of stylistic features in digitalslang language and their implications for language ethics among eleventh-grade students of Primbana Senior High School. This research is motivated by the widespread use of slang on social media, particularly tiktok, which influences students’ communication patterns. This study employs a qualitative approach with a content analysis design. The data consist of slang utterances obtained from videos, captions, and comments on tiktok, supported by questionnaires. Data collection techniques include observation using note-taking, recording, and non-participant observation methods. The data were analyzed using referential, orthographic, and pragmatic matching methods. The results show that there are 44 data of stylistic forms of slang, including loanwords, acronyms, neologisms, and nonstandard forms, as well as 20 data of stylistic meanings consisting of expressive, social, and pragmatic meanings. The use of slang reflects students’ creativity and social identity; however, excessive use may reduce the use of standard Indonesian and language politeness. Therefore, awareness is needed in using language appropriately according to context.